Evaluation of the Relation between Tuning Fork Tests, Glue ear Presence, and Conductive Hearing Loss in Patients with Otitis Media with Effusion - Rahmani, Zahra; Mokhtarinejad, Farhad; khajavi, Mahdi; Bazgir, Narges; Kordjazi, Mohammadsmaeil; Mohammadi, Mahya (Journal of Otorhinolaryngology and Facial Plastic Surgery, 2022)
Background: In the middle ear inflammation, otitis media with effusion (OME) leads to a sterile effusion. Although most OME resolves without any complications, long-lasting OME may cause conductive hearing loss (CHL). Aim: In this article, we investigate the validity of the Rinne and Weber tests in different frequencies of tuning forks in predicting the conductive hearing loss secondary to OME as diagnosed by more modern audiometric tests. Methods: A case series of 25 consecutive patients visited the Loqman Hakim Hospital clinic. Each patient was evaluated by tuning fork tests (256, 512, 1024, 2048 Hz), audiometry, tympanometry, and tympanocentesis. Results: In evaluation of the hearing status in OME patients, there was no significant association between the Weber test, audiometry, and tympanometry. The 256 Hz Rinne test correlated with the level of hearing loss in patients with OME. Results revealed no relationship between the presence of glue ear, audiometric, tympanometric, and tuning fork tests. Conclusion: 256 Hz Rinne test can predict the presence of CHL in cases suffering from OME. Adhesive otitis does not worsen the hearing condition of patients.